STUDENTS’ LEARNING STYLE IN READING COMPREHENSION AT THE TENTH GRADE STUDENTS AT SMA SWASTA TELADAN MEDAN TEMBUNG - Fani Maries F H Nst; Rita Suswati (Universitas Negeri Medan, 2017)
The purpose of conducting this research was find out whether the most dominantlearning style in reading comprehension and to find out which is the fasteststudents‟ learning style in reading comprehension at the tenth grade students atSMA SWASTA Teladan Medan Tembung in academic year 2016/2017. Therewere 239 students from 5 classes as the subject of this research. In this case, theresearcher collected the data by using learning style questionnaire andobservation. The result showed that auditory learning style is the most dominantlearning style at the tenth grade students at SMA SWASTA Teladan Medan, thepercentage was 52.30%, it means 125 from 239 students prefer to hear than readand move. The second was visual learning style, score 30.54% , means tha 73from 239 students prefer to read. Then, kinaesthetic learning style, the sore,17.15%, means that only 41 students prefer to move. For the fastest student‟s inreading comprehension came from visual students or visual learners. They getscore 55%, followed auditory 40%, and kinaesthetic 5%.